Fenton pre-oxidation of natural organic matter in drinking water treatment through the application of iron nails. Issue 17 (29th July 2022) - dos Santos, Naiara de O.; Teixeira, Luiz A.; Zhou, Qizhi; Burke, Grace; C. Campos, Luiza
ABSTRACT: This study investigated for the first time the efficiency of an advanced oxidation process (AOP) zero valent iron/hydrogen peroxide (ZVI/H2 O2 ) employing iron nails for the removal of Natural Organic Matter (NOM) from natural water of Regent's Park lake, London, UK. The low cost of nails and their easy separation from the water after the treatment make this AOP attractive for water utilities in low- and middle-income countries. The process was investigated as a pre-oxidation step for drinking water treatment. Results showed that UV254 removal in the natural water was lower than that of simulated water containing commercial humic acid (HA), indicating a matrix effect. Statistical analysis confirmed the maximum removal of dissolved organic carbon (DOC) in natural water depends on the initial pH (best at 4.5) and H2 O2 dosage (best at 100% excess of stoichiometric dosage). DOC and UV254 removals under this operational condition were 51% and 89%, respectively. Molecular weight (MW) and specific UV absorbance (SUVA254) were significantly reduced to 74% and 78%, respectively. Formation of Chloroform THM in natural water sample after the ZVI/H2 O2 process (initial pH 4.5) was below the limit for drinking water, and 48% less than the THM formation in the same water not subjected to pre-oxidation. Characterization of oxidation products on the iron-nail-ZVI surface after the ZVI/H2 O2 treatment by SEM, XRD, and XPS identified the formation of magnetite and lepidocrocite. Results suggest that the investigated ZVI/H2 O2 process is a promising technology for removing NOM and reducing THM formation during drinking water treatment.